2009
DOI: 10.1021/jf8037693
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nitrogen Supplementation and Saccharomyces Species on Hydrogen Sulfide and Other Volatile Sulfur Compounds in Shiraz Fermentation and Wine

Abstract: A Shiraz must with low yeast assimilable nitrogen (YAN) was supplemented with two increasing concentrations of diammonium phosphate (DAP) and fermented with one Saccharomyces cerevisiae and one Saccharomyces bayanus strain, with maceration on grape skins. Hydrogen sulfide (H(2)S) was monitored throughout fermentation, and a total of 16 volatile sulfur compounds (VSCs) were quantified in the finished wines. For the S. cerevisiae yeast strain, addition of DAP to a final YAN of 250 or 400 mg/L resulted in an incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
108
2
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(124 citation statements)
references
References 40 publications
12
108
2
2
Order By: Relevance
“…Chemical and microbiological analyses YAN was calculated as the sum of ammonia-derived nitrogen and FAN, and therefore did not include proline [25]. The fermentation progress was monitored by daily analysis of residual sugar by means of an enzymatic kit.…”
Section: Fermentationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemical and microbiological analyses YAN was calculated as the sum of ammonia-derived nitrogen and FAN, and therefore did not include proline [25]. The fermentation progress was monitored by daily analysis of residual sugar by means of an enzymatic kit.…”
Section: Fermentationsmentioning
confidence: 99%
“…Based on the observation that a negative correlation exists between naturally occurring nitrogen in the juice and total H 2 S formed during fermentation [28], one commonly adopted strategy to limit formation of H 2 S in wine fermentations is to provide adequate yeast assimilable nitrogen (YAN) to ensure sufficient availability of the amino acid precursors [reviewed in 1]. However, recent data have suggested that the addition of YAN to wine fermentations not only does not reduce H 2 S formation, but in some cases even appears to exacerbate the problem [14,25,26,29]. The observation, reported by the same authors, that this effect is also strain-dependent, suggests that interactions between YAN and the genetic background of individual yeasts are a key factor in determining the amount of H 2 S formed during fermentation.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, under these particular fermentation conditions, results here agree with previous reports that S 0 residues above 1 μg/g can increase H 2 S production (Thoukis andStern 1962, Wenzel et al 1980). However, at low S 0 concentrations, other factors such as juice nutrient status (Ugliano et al 2009) likely have a larger role in explaining differences in H 2 S production. Additionally, yeast strain will affect not only H 2 S production, but also the conversion efficiency of S 0 to H 2 S (Acree et al 1972).…”
Section: Figurementioning
confidence: 99%
“…The S 0 concentration necessary to cause problems is not well agreed upon, in part because H 2 S production is affected by factors other than S 0 concentration. H 2 S is produced during fermentation as a byproduct of amino acid synthesis during normal yeast (Saccharomyces cerevisiae) metabolism (Jiranek et al 1995), and this pathway can lead to differences in H 2 S production in the absence of S 0 residues, related to differences in juice nutrient status (Ugliano et al 2009), must turbidity, yeast strain (Rankine 1963), and fermentation temperature (Schutz and Kunkee 1977).…”
mentioning
confidence: 99%
“…However, recent works show there are other molecules than H 2 S, which can enhance the appearance of reductive notes in wines [14]. Rauhut and Kürbel [15,16] report that wines with sulfur aroma defects had increased concentrations of methanethiol (MeSH), ethanethiol (EtSH), dimethyl disulfide (DMDS), methyl ethyl disulfide (MeSSEt), diethyl disulfide (DEDS), thioacetic acid-S-methyl ester (MeSAc) and thioacetic acid-S-ethyl ester (EtSAc) as well as other known and unknown S-compounds.…”
Section: Introductionmentioning
confidence: 99%